History of higher education in Rio Grande do Norte and the inequality of access (Research, Society and Development, 2021)
This work refers to a research carried out by the Master's Degree Program in Education at the Federal University of Rio Grande do Norte. The study aims to understand and discuss the field of higher education in the State of Rio Grande do Norte and the inequality of access in the first bachelor's degree courses in the area of ​​education added to the University of Rio Grande do Norte (URN), in the period between the years 1958 to 1968. With the objective of researching the inequality of access of young people, who completed secondary school and could continue their higher education training, which this study is necessary. The Chronological Synthesis of UFRN 1958/2017 (Volume I) gives us support on the socio-historical context of education and especially on the subjects who entered higher education in this period. The Institutional Repository of the Federal University of Rio Grande do Norte, was the resource used to provide data in the development of this research, which is theoretical and methodologically based on cultural history, so this investigation will be documental and bibliographical. The study about inequality of access in higher education has meanings in the field of the history of education.